Research of address abroad: commentary to the judicial decree of the Provincial Court of Cordoba, of 17th June 2020 - Pérez de Colosía y Lázaro, Gloria (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
All legal proceedings must by necessity begin with the notification of the opposing party, which can sometimes be a complex problem to resolve if the defendant’s domicile is unknown or is incorrect, since it is necessary to safeguard both the right to defence and the right to effective judicial protection. In cross-border proceedings, this situation may be aggravated by the lack of legal instruments of the judicial bodies of the state of origin. This essay analyzes the judicial mechanisms for the investigation of domicile in international cases, based on the order issued by the Provincial Court of Córdoba due to the omission, on the part of a lower court, to execute such mechanisms and agree to annul the procedure.
Keywords: Regulation (EC) 1393/2007; Regulation (EC) 1206/2001; notification of judicial documents; address enquiries; international judicial cooperation in civil matters